Factors that contribute toward student’s satisfaction on blended learning in UiTM Kedah / Zur Ain Syahira binti Ghazaly ... [et al.] - Ghazaly, Zur Ain Syahira; Jamaluddin, NurHidayah (2018)
The research was conducted to study the factors that contribute toward student’s satisfaction on blended learning in UiTM Kedah. This study conducted to determine the level of student’s satisfaction on blended learning in UiTM Kedah and to identify the relationship between perceived usefulness, perceived ease of use and perceived enjoyment. This research applies a quantitative design in which the researcher relies on primary data gather throughquestionnaire. The entire questionnaire was administered at UniversitiTeknologi MARA (UiTM) Kedah between 10th and 12th week of semester September-January 2018. The application of questionnaires used to distribute among the diploma and bachelor degree students in UiTM Kedah. The total sample size used in this study is 363 respondents. The analysis of finding in this study are manage to answer all the objective stated. The finding of this study indicate the level of student’s satisfaction on blended learning is at the average level. All independent variable which are perceived usefulness, perceived ease of use and perceived enjoyment have significant relationship with student’s satisfaction on blended learning. The most significant factor that contribute toward student’s satisfaction on blended learning is perceived usefulness with the highest beta value. Therefore, to conclude there is a relationship between perceived usefulness, perceived ease of use, and perceived enjoyment, thus all the objective in this study is achieved.